2010 White Paper on Recent Issues in Regulated Bioanalysis & Global Harmonization of Bioanalytical Guidance. (December 2010) - Savoie, Natasha; Garofolo, Fabio; van Amsterdam, Peter; Bansal, Surendra; Beaver, Chris; Bedford, Patrick; Booth, Brian P; Evans, Christopher; Jemal, Mohammed; Lefebvre, Marc; Lopes de Silva, Arthur Leonardo; Lowes, Steve; et al.
The 4th Calibration and Validation Group Workshop on Recent Issues in Regulated Bioanalysis, a 2-day full immersion workshop, was organized by the Calibration and Validation Group. Contract research organizations, pharmaceutical companies and regulatory agencies came together to discuss several 'hot' topics concerning bioanalytical issues and regulatory challenges and to reach a consensus among panelists and attendees on many points regarding method validation of small and large molecules.